2003
DOI: 10.1088/0031-9155/48/21/009
|View full text |Cite
|
Sign up to set email alerts
|

Results supporting calculated wall correction factors for cavity chambers

Abstract: Thick walled cavity ionization chambers are used by primary standard laboratories as primary air kerma standards in 137Cs and 60Co gamma-rays. Application of the cavity theory requires correction for the effects of photon attenuation and scattering in the chamber walls. For more than a decade there have been intensive discussions about the validity of wall correction factors determined by more traditional extrapolation methods versus those calculated by Monte Carlo methods. For existing primary standards the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…33,34 The HRK-3 is one of PTB's primary standards for air kerma free in air for 60 Co and 192 Ir gamma radiation 35,36 based on the Bragg-Gray cavity theory.…”
Section: In Diameter)mentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 The HRK-3 is one of PTB's primary standards for air kerma free in air for 60 Co and 192 Ir gamma radiation 35,36 based on the Bragg-Gray cavity theory.…”
Section: In Diameter)mentioning
confidence: 99%
“…The calibration coefficient N LS01 Co-60 for 60 Co is derived by traceable calibration of the LS01 secondary standard chamber in a 60 Co reference field to a custom-built graphite walled cavity ionization chamber referred to as HRK-3. 33,34 The HRK-3 is one of PTB's primary standards for air kerma free in air for 60 Co and 192 Ir gamma radiation 35,36 based on the Bragg-Gray cavity theory.…”
Section: In Diameter)mentioning
confidence: 99%
“…14 -16 There is one particularly convincing experiment from the PTB which demonstrates that the linear extrapolation technique for determining K wall is inappropriate. 17 We have undertaken a sensitivity study to investigate the uncertainties associated with these calculated values, and the sensitivity of the calculated values to such things as the Monte Carlo code used, the 60 Co spectrum used, the diameter of the 60 Co source, and the distance from the source. As well as investigating K wall , we have undertaken to investigate the sensitivity of the calculated values of the other factors in Eq.…”
Section: Introductionmentioning
confidence: 99%
“…There has been concern about the proper way to determine the values of A wall . 14 This issue has recently been unequivocally resolved in favor of using the Monte Carlo calculated values [19][20][21] over the linear extrapolation technique used by Goetsch et al This has led to a change of about 1% in the NIST air-kerma standards for 137 Cs and 60 Co. 32 Table I presents values of A wall . The first observation is that the values "measured" using linear extrapolation for the graphite-walled thimble chamber are in good agreement with the Monte Carlo calculated values.…”
Section: B Accuracy Of a Wallmentioning
confidence: 99%
“…For this reason, we have resorted to the Monte Carlo method, which has been shown to estimate accurately both the dose inside the cavity of an ion chamber and A wall , the correction factor for attenuation and scatter in the chamber's wall. 3, [14][15][16][17][18][19][20][21] In particular, Seuntjens et al 17 demonstrated that EGSnrc calculates ion chamber response with an accuracy of 0.1% relative to its own cross sections down to a mean photon energy of about 100 keV which makes it an ideal tool for this work.…”
Section: Introductionmentioning
confidence: 99%